Apropiación de los espacios públicos urbanos del sub sector de la Colmena de la administración zona centro del distrito metropolitano de Quito - Lozada Ortega, Olga María (2015)
This research is an attempt to approach the urban actor in the moment when he appropriates public areas, for this case we have analyzed the “Parque Mancomunado” in the sub-sector of “La Colmena Barrio Santa Lucia Alta.” The purpose of this study is to inquire the usage and the social relations, between the users and the public area, the same that we see in the different forms of appropriation. The hypothesis which guide this investigation points that the users and the social relations of the public areas in use, affect directly upon the level of citizen appropriation of the public areas; if the participation only develops in consultative terms the level of appropriation will be minimum, while if the citizen intervenes in the deliberative process, execution, tracing and evaluation of the actions to be accomplish, not only the level of appropriation will be higher but also the democratic quality of the participative process. The urban public areas allows the encounter, the interaction, the social tissue and the cohesion between people, contributing in the process of interaction between diverse social groups and also the construction of a collective life sense. Although it´s importance, these areas are empty most of the time and as a result of that, delinquency starts raising.